2017
DOI: 10.1007/s00464-016-5384-x
|View full text |Cite
|
Sign up to set email alerts
|

Does stoma site specimen extraction increase postoperative ileostomy complication rates?

Abstract: SSE does increase stoma site complications. SSE should be used with caution, or in conjunction with other techniques to reduce hernias in patients requiring a permanent stoma or with an elevated BMI. The increase in stoma site complications does not translate into additional surgeries or postoperative sequelae following stoma reversal and is a reasonable option in patients requiring a temporary stoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 18 publications
2
29
3
Order By: Relevance
“…According to Li W Fig. 1 Flow-chart of evaluation of outcome et al, 2017, more complications with parastomal hernias were seen if the specimen was extracted at the stoma site in laparoscopic surgery, but no increase in stoma site hernia after stoma reversal [28]. In the present study, the hernia incidence was low, even though the majority of primary surgeries were performed by open surgery.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…According to Li W Fig. 1 Flow-chart of evaluation of outcome et al, 2017, more complications with parastomal hernias were seen if the specimen was extracted at the stoma site in laparoscopic surgery, but no increase in stoma site hernia after stoma reversal [28]. In the present study, the hernia incidence was low, even though the majority of primary surgeries were performed by open surgery.…”
Section: Discussionmentioning
confidence: 43%
“…Median BMI in patients with stoma site hernia was 28 (IQR: 25-29) kg/m 2 versus 25 (22)(23)(24)(25)(26)(27)(28) in patients without hernia (p = 0.026) ( Table 4). Of the 16 patients with hernia, 14 (88%) were men and 2 (12%) were women, versus 116 (58%) men and 84 (42%) women in patients without hernia (p = 0.031).…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, Li et al . reported that ileostomy formation at the SES should be performed with caution because of increased incidence of stoma site complications 8 . In this study, temporary ileostomy formation at the SES was associated with a shorter operation time and less wound complication rate than the control group, which is similar to that reported by Karakayali et al .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al . claimed that forming a stoma at the SES can increase the risk of stoma-related complications and that it is safe to perform ileostomy at a different location 8 . However, research on complication rates when a stoma is formed at the SES in patients with rectal cancer is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al have shown that stoma site specimen extraction is associated with an increased risk of parastomal hernia, but not with need for further surgeries, and this technique is therefore still a reasonable option in patients requiring temporary stomas. 34 Extraperitoneal tunneling, an alternative technique for stoma creation first described by Goligher in 1958, has been shown to be associated with a lower rate of parastomal hernia formation particularly in patients undergoing laparoscopic abdominoperineal resection with end colostomy. 3,32,35,36 Further prospective randomized studies are needed to better define which subset of patients benefit most from this technique given the increases in operative time and postoperative complications associated with its use.…”
Section: Parastomal Herniamentioning
confidence: 99%